Orthopaedic surgery : principles of diagnosis and treatment - Wiesel, Brent B. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
"The book is divided into two sections. The general principles portion presents orthopaedic basic science in sufficient detail to prepare the reader for the in-training and board examinations. It contains chapters on the basics of the various modalities commonly used for patient evaluation in orthopaedics and the evaluation and treatment of musculoskeletal infection, metabolic bone disease, and musculoskeletal oncology. In addition, an overview of rheumatologic diseases affecting the musculoskeletal system and the principles guiding the treatment of orthopaedic trauma and sports medicine patients are included. In the subspecialty section, each chapter addresses the functional anatomy, patient evaluation (history, physical examination, and imaging), traumatic injuries, and atraumatic conditions for a specific region of the body. For each diagnosis, the typical presentation, options for non-operative and operative management, and expected outcomes are discussed"--Provided by publisher.